BIOLOGICAL RESPONSE OF COWPEA BRUCHID, CALLOSOBRUCHUS MACULATUS (FAB.) (COLEOPTERA: BRUCHIDAE) TO COUMARIN EXTRACTS - Ismail, I. A.; El-Gengaihi, S. E.; Affifi, A. (European Scientific Journal, ESJ, 2014)
Cowpea beetle, Callosobruchus maculatus (Fab.) (Coleoptera: Bruchidae), is the most important storage pest of cowpea. The effect of ethanol and chloroform extracts of murraya, kumquat and celery plants on the various biological aspects of Cowpea beetles was studied. Kumquat, ethanol extract was most efficient extract which affected significantly the fecundity of the females followed by murraya. Celery may have an attractant effect on adults; however, it induced the higher mortality. Longest longevity was recorded in the treatment with 1% murraya chloroform extract. On the other hand, the shortest longevity was obtained with the higher concentration of kumquat and celery alcohol and chloroform extracts. Kumquat was the potent one to deter the insect from laying eggs as confirmed by the higher calculated oviposition Deterrence index. The minimum values were gained from chloroform and ethanol extracts at concentration of 4.0% of celery. On the other hand, highest percentage of egg hatchability was recorded for chloroform and ethanol extracts of murraya at 1% concentration, respectively. The data revealed insignificant extension of the duration of immature individuals on using different extracts in comparison with the control. Also, no significant difference existed between different extracts. Maximum percentage of adult emergence (survival) was obtained on using 1% chloroform extract of Kumquat. The least survival was obtained on using 4% ethanol extract of murraya and celery.